Structural elements in the flexible tail of the co-chaperone p23 coordinate client binding and progression of the Hsp90 chaperone cycle - Maximilian M. Biebl; Abraham Lopez; Alexandra Rehn; Lee Freiburger; Jannis Lawatscheck; Birgit Blank; Michael Sattler; Johannes Buchner (Nature Communications, 2021)
p23 is a co-chaperone of Hsp90 but its mode of action is mechanistically not well understood. Here, the authors combine in vitro and yeast in vivo assays, biochemical measurements and NMR experiments to characterize p23 and identify two conserved helical elements in the intrinsically disordered C-terminal tail of p23 that together with the folded domain of p23 regulate the Hsp90 ATPase activity and affect the binding and maturation of Hsp90 clients.